Legal Position of Power of Attorney Imposing Mortgage Rights in Subsidized Home Ownership Credit Facilities - Rozaqi, Muh (Jurnal Konstatering, 2024)
A Power of Attorney to Encumber Mortgage Rights is a letter containing a power of attorney made or given by the collateral provider or land owner, in this case the debtor as the party providing the power of attorney to the creditor as the party receiving the power of attorney to represent the power of attorney in granting mortgage rights to the creditor over the land belonging to the power of attorney. . Regarding SKMHT, a time period is set for the SKMHT to be followed into a Deed of Granting Mortgage Rights (APHT). In practice, based on the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency Number 22 of 2017 concerning Determination of Time Limits for the Use of Power of Attorney to Encumber Mortgage Rights to Guarantee Repayment of Certain Credits, the SKMHT is valid until the end of the main agreement, one of which is Subsidized Home Ownership Credit. This research aims to find out and explain the procedures for making SKMHT in subsidized home ownership credit facilities at Bank BNI Pekalongan Branch, to find out and explain the legal position of SKMHT in subsidized home ownership credit at Bank BNI Pekalongan Branch and to find out and explain the legal consequences of SKMHT for defaulting debtors at Bank BNI Pekalongan Branch, the research approach used in this thesis is an empirical juridical legal research method which relies on primary data (field research) and the research specifications applied in this research are analytical descriptive with a population and the sampling technique used is Non Random Sampling with purposive sampling. This research shows that the procedure for making SKMHT must be made specifically and authentically before a Notary/PPAT, preceded by the signing of a credit agreement. The function of SKMHT as a Power of Attorney is addressed to the holder of mortgage rights or another party to represent the person giving the mortgage rights. In the event that the debtor defaults, the recipient of the power of attorney can proceed with making a Deed of Granting Mortgage Rights so that the creditor is the preferred creditor.